Pengembangan UMKM Berkelanjutan: Pemanfaatan Produk Lokal dan Teknologi untuk Meningkatkan Daya Saing di Era Ekonomi Digital - Budi Siswanto; Briliana Maulidya; Marcellina Elka Suryana; Muhammad Izzan Musyaffa; Zanuba Arifatul Nur Afidah (Politeknik Piksi Ganesha Indonesia, 2025)
Gemuh Village is a village located in Pecalungan Subdistrict, Batang Regency, Central Java Province. The geographical location of Gemuh Village is quite strategic because it is flanked by several villages and has good natural conditions with fertile soil, thus making this village have great potential as a producer of agricultural commodities such as cassava, cloves, tea, melinjo, coffee, and sengon wood. Through the utilization of information and communication technology to market MSME products in Gemuh Village. In this research, several efforts have been made to support MSMEs that have great potential in Gemuh Village, namely Ayo Maju Bersama UMKM Digital, MSME Branding Video Making, and MSME Assistance. Some of these programs are expected to be able to support the community in marketing and contacting customers for more MSME products by utilizing information and communication technology. Through the UNS Thematic KKN Group in Gemuh Village, they have involved local residents to participate in socialization activities, with the intention of maximizing the potential owned by Gemuh Village.